Footnotes, Bob Fosse's Broadway Book reviews - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 1998)
Dance photo books.
Footnotes: a memoir. Tommy Tune, Simon & Schuster, 1997. Bob Fosse's Broadway. Margery Beddow, Heinemann, 1996.